Ultrastructural studies on infection processes by Colletotrichum acutatum on guava fruit - K. N. BORA, M. DAS and (Indian Phytopathology, 2002)
C. acutatum was identified on stored guavas from Assam, India. The fruits rotted completely within 7-10 days, depending upon the temperature and humidity. Symptoms of infection appeared as brown lesions on fruits with a pinkish spore mass. The infection process was studied by light and scanning electron microscopy. Infection hyphae grew directly from conidia and entered the fruit wall through stoma or they directly penetrated the cuticle. Subsequent intercellular and intracellular development of the fungus resulted in the rapid degradation of the cell wall and membranes structural integrity leading to cell collapse and ultimately the formation of acervuli which pierced the fruit cuticle.